Relapsing encephalopathy in a patient with α-methylacyl-CoA racemase deficiency. Issue 4 (21st November 2007) - Thompson, S A; Calvin, J; Hogg, S; Ferdinandusse, S; Wanders, R J A; Barker, R A
Abstract : α-Methylacyl-CoA racemase (AMACR) deficiency is a rare disorder of fatty acid metabolism which has recently been described in three adult cases. We have identified a further patient with clinical features of a relapsing encephalopathy, seizures and cognitive decline over a 40 year period. Biochemical studies revealed grossly elevated plasma pristanic acid levels, and a deficiency of AMACR in skin fibroblasts. Sequence analysis of AMACR cDNA identified a homozygous point mutation (c154T>C). This case adds to the phenotypic variation seen in this peroxisomal disorder and highlights the importance of screening for plasma pristanic acid levels in patients with unexplained relapsing encephalopathies.